The experiment in the history of economics - Philippe Fontaine; Robert Leonard (Routledge, 2005)
Throughout the history of economic ideas, it has often been asserted that experimentation is impossible, yet, in fact, history shows that the idea of 'experimentation' has always been important, and as such has been interpreted and put to use in many ways. Rich in historical detail, the essays in this topical volume deal with such issues as laboratory experimentation, the observed transition from a post-war economics to a contemporary discipline, the contrasting positions of Friedrich Hayek and Oskar Morgenstern, the socio-economic experiments proposed by Ernest Solvay and Knut Wicksell, and a rigorous examination of the way in which economic models can or cannot be construed as valid experiments producing useful knowledge. A testament to the variety of ways in which experimentation has been of importance in the creation of economic knowledge, these wide-ranging essays will interest those seeking to expand their historical understanding of the discipline, be they theorists, historians, philosophers, advanced students or researchers.
Keywords: 330; Experiment; Ökonomische Ideengeschichte